2022
DOI: 10.3390/ijerph19137948
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Campus-Built Environment and Physical Fitness in College Students in Xi’an—A GIS Approach

Abstract: Background: This research aimed to investigate the correlation between students’ physical fitness and campus-built environment, which could put forward some suggestions for the construction of a campus environment. Method: Four colleges in Xi’an were regarded as special “semi-closed” spaces. Combined with ArcGIS and SPSS, the correlation between the built environment of colleges and the students’ physical fitness test results in 2019 was analyzed (n = 1498). Results: regarding the men questioned in this resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…The built environment has a role in shaping healthy behavior outcomes [92,93]. This indicates that the built environment (urban planning, land use) and physical activity are clearly associated [94]. Therefore, there is a relationship between the campus built environment and physical activity [95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The built environment has a role in shaping healthy behavior outcomes [92,93]. This indicates that the built environment (urban planning, land use) and physical activity are clearly associated [94]. Therefore, there is a relationship between the campus built environment and physical activity [95].…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the built environment (urban planning, land use) and physical activity are clearly associated [93]. Therefore, there is a relationship between the campus built environment and physical activity [94]. Moreover, physical activity has a positive impact on human health through cardiovascular health and combined built environment strategies to improve public health [95].…”
Section: Discussionmentioning
confidence: 99%
“…Kebugaran fisik merupakan salah satu faktor penting untuk menunjang melakukan aktivitas fisik yang maksimal. Kebugaran fisik menurut (Jariono et al, 2021;Wulandari, Wulandari, Gatot, 2022); (Kidokoro et al, 2022;Lu et al, 2022;Ras et al, 2022) merupakan unsur yang sangat penting hampir di seluruh cabang olahraga. Oleh karena itu latihan kondisi fisik perlu mendapat perhatian yang serius direncanakan dengan matang dan sistematis sehingga tingkat kebugaran jasmani lebih baik.…”
Section: Pendahuluanunclassified
“…In the databases of Web of Science, BIOSIS Citation Index, MEDLINE, and CSCD, we found seventeen articles on the walkability of university campuses by using the keywords "walkability", "campus", and "university". Eight of these articles discussed the association between campus walkability and student or campus employee physical activity, and all consistently concluded that high walkability is associated with increased student physical activity and lower body mass index (BMI) [26][27][28][29][30][31][32][33]. Two articles discuss the correlation between campus walkability and the built environment, trying to find the factors that affect walkability [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Still, the Walk Score they used was calculated using the Euclidean distance between facilities as the primary data. Lu et al, using an improved walking index [29], added two parameters, green space per capita and land use combination, into the calculation and conducted a correlation analysis between the calculation results and the results of college students' physical system tests, and found that campus walkability was positively correlated with college students' physical fitness, but they also used Euclidean distance between facilities. According to Tsiompras and Photis [43], using the inter-facility network distance measured by the actual walking network as the data source is more accurate and correlates better with human physical activity than using Euclidean distance as the data source.…”
Section: Introductionmentioning
confidence: 99%